81 Antiphospholipid syndrome in systemic lupus erythematosus leads to a more severe disease. (April 2019) - Riancho-Zarrabeitia, Leyre; Martínez-Taboada, Víctor M; Figueroa, Iñigo Rua; Alonso, Fernando; Izquierdo, Maria Galindo; Ovalles-Bonilla, Juan; Olivé-Marqués, Alejandro; Nebro, Antonio Fernandez; Calvo, Jaime; Narváez-García, Javier; Muriel, Eva Tomero; Isacelaya, Esther Uriarte; et al.
Abstract : Background: Antiphospholipid antibodies (aPL) have been associated with organ damage and certain features in systemic lupus erythematosus (SLE) patients. Our aim was to investigate the differences between SLE patients according to the presence of aPL and/or clinical antiphospholipid syndrome (APS). Methods: Patients from the RELESSER-T registry were included. RELESSER-T is a multicenter, hospital-based registry, with retrospective cross-sectional collection of data from a large representative sample of adult non-selected patients with SLE attending Spanish rheumatology services from the public national health system. Results: We included 3651 SLE patients and 1368 were positive for aPL (44.9% of patients were positive for anticardiolipin antibodies, 27.3% showed positivity for anti b2glycoprotein I and 24% for lupus anticoagulant). Overall 2283 patients were classified as SLE no aPL, 528 as SLE-APS and 840 as SLE-aPL. Demographic data, clinical and laboratory features in the different groups are showed in table 1 . Regarding cardiovascular risk factors, SLE-APS patients had higher rates of hypertension, dyslipidemia and diabetes than SLE-aPL and SLE no aPL patients (p<0.001, p<0.001 and p=0, 022, respectively). SLE-APS patients showed a lower prevalence of photosensitivity and higher frequencies of serositis, proteinuria (>0.5 grs), urinary cell casts, seizures and psychosis (p0.001). Overall, SLE-APS patients showed a lower rate of cutaneous manifestations and higher rates of neuropsychiatric, cardiac, pulmonary, renal, joint and ophthalmological manifestations (table 1 ). In accordance with a more severe clinical profile, higher frequency of anti-DNA antibodies and hypocomplementemia were observed in the SLE-APS group (p<0.001). In addition to a higher disease activity (SLEDAI), SLE APS patients presented more damage accrual with higher values in SLICC (1.9±2.2 in SLE APS, 0.9±1.4 in SLE aPL and 1.1±1.6, p<0.001) and Katz indexes (3±1.8 in SLE APS, 2.7±1.7 in SLE aPL and 2.6±1.6 in SLE no aPL, p<0.001). Conclusions: SLE-APS patients show a more severe clinical profile with higher frequency of major organ involvement and more damage accrual than SLE-aPL and SLE no APL. Funding Source(s): None